Student relationship management in Germany: Foundations and opportunities - Andreas Hilbert; Karoline Schönbrunn; Sophie Schmode (Management Revue, 2007)
The objective of the article is to introduce to the topic of Student Relationship Management (SRM) in Germany. The concept has been derived from the idea of a Customer Relationship Management (CRM), which has already been successfully implemented in many enterprises. Its objective is to canvass for customers, obtain their loyalty towards the company and, if necessary, win them back. Furthermore, potential uses of a SRM within the context of Higher Education Management will be demonstrated by means of examples of German universities and by applying new methods.
Keywords: 650; Student Relationship Management; Customer Relationship Management; Higher Education Management; data mining; student satisfaction